Animais peçonhentos: uma análise de livros didáticos do PNLD 2020 - MADALENO, Kassia de Oliveira (Universidade Federal do Tocantins, 2023)
The textbook (LD) is still the main didactic tool available throughout Brazil's territorial extension in basic education. The LD is an important disseminator of information, being decisive for the formation of critical and conscious students, and should promote accurate, complete and broad knowledge about the different areas of Science. Thus, the present study aimed to analyze the textbooks, indicated in the National Plan for Textbooks (PNLD) of 2020 for the teaching of Sciences at Elementary School, referring to the contents of venomous animals whose accidents constitute a serious public health problem in Brazil and it is considered a scarce topic to be addressed within the school environment. The qualitative study used the method of bibliographic research and content analysis to evaluate seven of the twelve books discriminated in the PNLD 2020 in relation to the theme “Animals Venomous”. The textbook targeted for the analysis of the work were more specifically the volumes of the seventh year of Elementary School where the theme is addressed. The analysis of Science textbook, approved by PNLD 2020, revealed that the content of venomous animals is present in a fragmented way or is non-existent, and that it does not contemplate the great diversity, ecological, medical, economic and pharmaceutical importance of these animals for the community.